Establishment of Biotechnology Unit in Tribhuvan University: A Conceptual Approach - Manandhar, Gaurishankar (Tribhuvan University Journal, 2010)
Available with full-text. Key words: Biotechnology Unit; Tribhuvan University; Nepal Tribhuvan University Journal Volume XVI, 1993 Page: 35-49 Uploaded date: 3 October, 2010